Empowering Senior High School Students in Chemistry: Integrating 21st Century Skills - Tanghal, Analiza B.; Mendoza Jr., Joselito P. (Institut Agama Islam Negeri Kendari, 2025)
This quasi-experimental study investigated the effectiveness of integrating 21st century approaches in enhancing the skills and academic performance of grade 12 senior high school students, specifically those under the Academic Track-General Academic Strand (GAS), in General Chemistry 1 in San Miguel, Bulacan. Utilizing pre-test/post-test assessments, questionnaires, web-based learning platforms, class-wide peer tutoring, paired peer tutoring, and contextualized laboratory resources, students' skills, academic performance, and perceptions towards the use of 21st century approaches were evaluated. Results indicated that the implementation of 21st century approaches led to improvements in students' communication, collaboration, critical thinking, and creativity skills in General Chemistry 1. There was a notable increase in academic performance, as evidenced by significant differences in pre-test and post-test scores among Grade 12 students. Students expressed positive perceptions regarding the beneficial impact of 21st century approaches on their studies.